PP.26 Sustainable Volunteering and Its Effect on Ugandan Stillbirth Rates. (26th April 2013) - MacLeod, K; Ackers, L
Abstract : Background: The Ugandan Maternal and Newborn Hub is a THET funded initiative focused on implementing Sustainable Volunteering Projects (SVPs) to improve maternal and newborn health. Annually, there are 2·65 million stillbirths worldwide and almost 90% occur in low-resource settings. Up to 70% of stillbirths occur in the intrapartum period; frequently these are associated with suboptimal care. Methods: Through a SVP, from January to June 2012, we undertook a quality improvement project aiming to reduce intrapartum stillbirths at Mbarara Hospital in Uganda. Our quality improvements included regular audit presentations, implementation of a labour ward board and skills and drills training. We classified suboptimal care into types of delay using Thaddeus & Maine Three Delay Model. Results: In this 6 months period, there were 102 intrapartum stillbirths. Most stillbirths were singleton pregnancies (99%) with a mean maternal age of 24 years and a mean parity of 2. 34% of women were unbooked. Suboptimal factors contributing to intrapartum stillbirths were identified in 86.4% of cases, 22% were related to care whilst admitted. Intrapartum stillbirths occurring after hospital admission reduced after introduction of quality improvement measures: see table . Discussion: Basic and comprehensive emergency obstetric care is an important intervention to reduce intrapartum stillbirths in the developing world. SVPs are an effective way of individualising quality improvement measures and improving outcomes.